Effects of seawater mixing on the mobility of trace elements in acid phosphogypsum leachates. (February 2018) - Papaslioti, Evgenia-Maria; Pérez-López, Rafael; Parviainen, Annika; Sarmiento, Aguasanta M.; Nieto, José M.; Marchesi, Claudio; Delgado-Huertas, Antonio; Garrido, Carlos J.
Abstract: This research reports the effects of pH increase on contaminant mobility in phosphogypsum leachates by seawater mixing, as occurs with dumpings on marine environments. Acid leachates from a phosphogypsum stack located in the Estuary of Huelva (Spain) were mixed with seawater to achieve gradually pH 7. Concentrations of Al, Fe, Cr, Pb and U in mixed solutions significantly decreased with increasing pH by sorption and/or precipitation processes. Nevertheless, this study provides insight into the high contribution of the phosphogypsum stack to the release of other toxic elements (Co, Ni, Cu, Zn, As, Cd and Sb) to the coastal areas, as 80–100% of their initial concentrations behaved conservatively in mixing solutions with no participation in sorption processes. Stable isotopes ruled out connexion between different phosphogypsum-related wastewaters and unveiled possible weathering inputs of estuarine waters to the stack. The urgency of adopting effective restoration measures in the study area is also stressed. Graphical abstract: Highlights: Contaminants released from phosphogypsum (PG) often reach coastal environments. PG-leachates revealed slow and demanding acid neutralisation during seawater mixing. As, Cd, Co, Cu, Ni, Sb and Zn remained mobile during seawater mixing even at pH 7. Non-conservative Al, Cr, Fe, Pb and U undergo precipitation and sorption processes. PG-related pollutants contribute highly to the contamination in Estuary of Huelva.